The knowledge of Iraqi Dentist about the diagnosis of common orallesions (Bangladesh Journal of Medical Science, 2020)
Background: the scientific knowledge of dentist regarding the diagnosis of common oral lesions may vary. Oral aphthous ulceration, oral lichen planus, pyogenic granuloma and oral irritating fibroma are common oral lesions.Objectives: The aim of this study is to assess the knowledge of Iraqi dentist about the ability to diagnose the common oral lesions.Materials and methods: A two hundred and seventy-eight dentist from both the health and education sectors were including in the questionnaire. The questionnaire included four pictures of common oral lesion that the dentist might see during his daily work and the question was (what is the most probable diagnosis?)Results: The overall assessment of knowledge of dentist regarding the four oral lesions is shown in table (6) with the higher mean of score for the diagnosis of aphthous ulceration (1.75), while the least mean of score was for the diagnosis of lichen planus (1.61). The total mean of scores of the knowledge of all dentists for the diagnosis of the four oral lesions was moderate (1.66).Conclusions: This study showed that the Iraqi dentist’s knowledge about the diagnosis of lichen planus, pyogenic granuloma and fibroma was moderate knowledge, while for the diagnosis of aphthous ulceration the assessment was good and better than other lesions.Bangladesh Journal of Medical Science Vol.19(2) 2020 p.304-309